Pupils' attitudes for physical education lesson and science lesson at primary schools: A comparative example of ankara province - Korkmaz, Murat; Yücel, Ali Serdar; Kiliç, Bülent; Çatikkaş, Fatih; Tuna, Dilek Cesim (American-Eurasian Network for Scientific Information, 2014)
The aim of this study is to examine primary school pupils' attitudes for physical education and science lessons in a comparative and applied fashion. Totally (N=452) primary school pupils participated in our study. Participants were selected randomly. In this applied study, a questionnaire with 5-point likert scale that consisted of two parts for the two lessons was administrated. Data as a result of the study were subject to reliability analysis, and the Cronbach Alpha coefficient was found as 0.921. Kaiser-MeyerOlkin, Barlett's Test of Sphericity analysis, Scree Plotgraph, Factor analysis, Correlation analysis, Tukey, and t-test were applied. It was found that the research was meaningful with Item-Total correlations having a p<0.01 significance level. As a result of the study, it was found that participants performed greater attitudes and importance for science, displayed higher interest and attention towards science lessons, and had thoughts that they will need science lessons more in the future. As for their attitudes for physical education lesson, it was seen that they were lower than those for science lessons. Among the main reasons are ideas and opinions that pupils do insufficient sports activities, sports equipment and materials are insufficient, and sports areas are ineligible for the types they wish to do. © 2014 AENSI Publisher All rights reserved.
Keywords: Attitude; Comparison; Importance; Interest; Lesson; Primary; Pupil; Science; Sports